Linking theory with practice on an MA TESOL programme - Bell, Douglas (N/A, 2021)
While there can be little doubt that taking part in an MA TESOL programme is likely to expose the participants to significant amounts of ELT theory, the learning that ultimately results from this may not always convert very well into ELT practice. This is particularly true for those who join a Masters’ programme with limited previous teaching experience, especially if the programme itself lacks a practical teaching component. In such cases, unless students are encouraged to make their own explicit links between theory and practice, the didactic transmission mode of delivery commonly found in university lectures may further conspire to make the gap even wider. This paper describes an attempt to move beyond such a traditional MA lecture format and discusses an alternative pedagogical means of linking theory with practice on an MA TESOL programme delivered at an EMI branch campus in China.